Experimental test of the geometric model of image formation in bright‐field microscopy. (15th February 2021) - Clements, RJ; Davidson, M; Model, MA
Abstract: In the geometric optics approximation, an image formed by an objective lens replicates the distribution of intensity at the front focal plane of the objective. Although this fact represents a fundamental optical principle, its application to analysis of bright‐field microscopic images was developed only recently and has not been tested experimentally. In this paper, we applied simple ray tracing to compute an image of a glass cylinder at various positions of the objective and to compare it to the experiment. We obtained a close match between theory and observation, except for a slight underestimation of the intensity in the middle part of the cylinder. The likely reason for this minor difference was constructive interference due to lens‐like properties of a cylinder, which could not be accounted for by geometric approximation. We expect that such artefacts would be negligible in imaging of live cells, and the geometric approach would successfully complement the existing quantitative phase methods. Lay Description: It has become customary to analyse microscopic images in terms of diffraction theory. However, when one is not interested in resolving fine details of an image, a much simpler and more intuitive geometric analysis based on ray tracing can be adequate. We applied geometric approach to analysis of bright‐field images of a small glass cylinder at different positions of the objective. Such an object would be very difficult to analyse using diffraction theory because of its high refractive index and steep boundaries. However, ray tracing produced a good match between theory and experiment. It can become a promising approach in bright‐field applications, such as quantitative phase imaging.